Impact of extracellular matrix stiffness on genomic heterogeneity in MYCN-amplified neuroblastoma cell line - López-Carrasco, Amparo (J Exp Clin Cancer Res, 2020)
BACKGROUND: Increased tissue stiffness is a common feature of malignant solid tumors, often associated with metastasis and poor patient outcomes. Vitronectin, as an extracellular matrix anchorage glycoprotein related to a stiff matrix, is present in a particularly increased quantity and specific distribution in high-risk neuroblastoma. Furthermore, as cells can sense and transform the proprieties of the extracellular matrix into chemical signals through mechanotransduction, genotypic changes related to stiffness are possible. METHODS: We applied high density SNPa and NGS techniques to in vivo and in vitro models (orthotropic xenograft vitronectin knock-out mice and 3D bioprinted hydrogels with different stiffness) using two representative neuroblastoma cell lines (the MYCN-amplified SK-N-BE(2) and the ALK-mutated SH-SY5Y), to discern how tumor genomics patterns and clonal heterogeneity of the two cell lines are affected. RESULTS: We describe a remarkable subclonal selection of genomic aberrations in SK-N-BE(2) cells grown in knock-out vitronectin xenograft mice that also emerged when cultured for long times in stiff hydrogels. In particular, we detected an enlarged subclonal cell population with chromosome 9 aberrations in both models. Similar abnormalities were found in human high-risk neuroblastoma with MYCN amplification. The genomics of the SH-SY5Y cell line remained stable when cultured in both models. CONCLUSIONS: Focus on heterogeneous intratumor segmental chromosome aberrations and mutations, as a mirror image of tumor microenvironment, is a vital area of future research.